THE WORK ENVIRONMENT AND SATISFACTION OF EMPLOYEES OF THE NATIONAL INSTITUTE MATERNAL PERINATAL - Tito Huamaní, Pedro Leonardo (2015)
This research was conducted at the National Institute Maternal Perinatal (INMP), where members of senior management played a major role in providing for the completion of fieldwork. This general objective research to ascertain and assess the level of perception of organizational culture and climate between INMP workers; and as specific objectives to differentiate the levels of perception of climate and culture as areas and occupational groups. In the same way as the elements of leadership, innovation, reward, comfort, decision making, communication, payment, identity, conflict and cooperation, motivation, influence the determination of culture and working environment. In a survey fieldwork had doc workers and professionals institution applies. The survey was supplemented with in-depth interviews aimed at managers, who in most cases corroborated the results obtained through the surveys. The results are highly encouraging, because it could test hypotheses raised and these have to do with the behavior of the leaders, improving communication, reciprocity between co-workers; other aspects that make up a particular work environment, which in turn feeds back to culture Specialized Maternal Perinatal Institute.